Aerospace series. Steel X12CrNiMoV12-3 (1.4938). Air melted and consumable electrode remelted. Hardened and tempered. Bars. De ≤ 150 mm. 900 MPa ≤ Rm ≤ 1 100 MPa. (18th May 2021) - British Standards Institution
No abstract available